Makna Simbolik Ritual Nyerah dan Namatkon Bacoan pada Upacara Peusenat dalam Masyarakat Keluwat - Muzain, Akhwanto; Muslim, Azis; Atsarissalaf, Muhyi (Prodi Sosiologi FISIP Universitas Teuku Umar, 2023)
This article discusses Clifford Geertz's theory of symbolic interpretivism by taking the nyerah and namatkon bacoan rituals at the peusenat ceremony in the Keluwat tribe in South Aceh district as the object of study. In social life, the Keluwat tribe views every procession carried out in rituals as having its own meaning and purpose. This research is descriptive with a qualitative approach and uses ethnographic design, data analysis using the interpretative model by Clifford Geertz. The results showed that the nyerah ritual is a form of glorification of the teacher as a healer who handles problems in the form of safety, healing and health. While the namatkon bacoan ritual is a proof that the child who will be circumcised will grow up, this ritual is also a sharia which is then made a tradition by the Keluwat community. The meaning of symbols in the nyerah and namatkon bacoan rituals emically is a hope, prayer, and message conveyed by parents. The symbolic meaning in terms of ethics is syncretism and mechanical solidarity.